Solve the equation.
x/5 + 9 = 4
A. 65
B. –25
C. 5
D. 20

Question

Asked 1/4/2013 6:24:09 PM

Updated 9/1/2014 6:26:14 AM

1 Answer/Comment

Flagged by andrewpallarca [9/1/2014 6:26:14 AM]

g
googletag.cmd.push(function() { googletag.display('div-gpt-ad-1564665647093-0'); });

Question

Asked 1/4/2013 6:24:09 PM

Updated 9/1/2014 6:26:14 AM

1 Answer/Comment

Flagged by andrewpallarca [9/1/2014 6:26:14 AM]

Rating

5

The answer for the equation x/5 + 9 = 4 is -25.

x/5+9=4

x/5=4-9

x/5=-5

x=-25.

x/5+9=4

x/5=4-9

x/5=-5

x=-25.

Added 9/1/2014 6:24:41 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [9/1/2014 6:26:19 AM]

Solve the equation.
6 = 2(x + 8) - 5x
A. 2/3
B. 3 1/3
C. - 2/3
D. -3 1/3 **Weegy:** -3 -3
Divide each term in the inequality by 3.
(3(5x-16))/(3)>-(3)/(3)
Simplify the left-hand side of the inequality by canceling the common factors.
5x-16>-(3)/(3)
Simplify the right-hand side of the inequality by simplifying each [ term.
5x-16>-1
Since -16 does not contain the variable to solve for, move it to the right-hand side of the inequality by adding 16 to both sides.
5x>16-1
Subtract 1 from 16 to get 15.
5x>15
Divide each term in the inequality by 5.
(5x)/(5)>(15)/(5)
Simplify the left-hand side of the inequality by canceling the common factors.
x>(15)/(5)
Simplify the right-hand side of the inequality by simplifying each term.
x>3
c. x > 3 is the answer. ] **User:** Solve the equation.
x - 9 = -6x + 5
A. 14
B. 7
C. 2
D. 21 **Weegy:** The answer is x=2. (More)

Question

Updated 1/5/2013 7:39:25 AM

4 Answers/Comments

6 = 2(x + 8) - 5x

6 = 2x + 16 - 5x

3x = 16- 6 = 10

x = 10/3 = 3 1/3

The solution for the equation 6 = 2(x + 8) - 5x is B. 3 1/3

6 = 2x + 16 - 5x

3x = 16- 6 = 10

x = 10/3 = 3 1/3

The solution for the equation 6 = 2(x + 8) - 5x is B. 3 1/3

Added 1/5/2013 3:51:57 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [9/1/2014 6:27:41 AM]

x - 9 = -6x + 5

x + 6x = 5 + 9

7x = 14

x = 14/7 = 2

The solution for the equation. x - 9 = -6x + 5 is C. 2

x + 6x = 5 + 9

7x = 14

x = 14/7 = 2

The solution for the equation. x - 9 = -6x + 5 is C. 2

Added 1/5/2013 3:59:47 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [9/1/2014 6:28:14 AM]

Okay, thank you. i just got to know i should also flag it even though the last auto answer is right [smile].

Added 1/5/2013 7:39:26 AM

Solve the system of equations by graphing.
-1/3x + y = –1
y = 4 + 1/3x
A.
infinitely many solutions
B.
no solution
C.
no solution
D. **Weegy:** 9x^4. If you are satisfied with my answer, please click 'Good' on the ratings. Thank you! (More)

Question

Updated 1/5/2013 7:00:45 AM

1 Answer/Comment

We replace y (= 4 + 1/3x) in the equation -1/3x + y = –1 we can get

-1/3x + 4 + 1/3x = –1

Simplify the equation we get 5 = 0

We all know that 5 could never be equal to 0

That is to say, there is no solution for -1/3x + y = –1 and y = 4 + 1/3x

-1/3x + 4 + 1/3x = –1

Simplify the equation we get 5 = 0

We all know that 5 could never be equal to 0

That is to say, there is no solution for -1/3x + y = –1 and y = 4 + 1/3x

Added 1/5/2013 7:00:45 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [9/1/2014 6:28:46 AM], Rated good by andrewpallarca

2(x 4)=30
A. 7
B. 11
C. 15
D. 19

Question

Updated 5/19/2015 6:18:25 AM

1 Answer/Comment

2(x + 4) = 30

x + 4 = 15

x = 15 - 4

x = 11

x + 4 = 15

x = 15 - 4

x = 11

Added 5/19/2015 6:18:25 AM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [5/19/2015 4:05:37 PM]

34,823,394

questions answered

There are no comments.